Analysis of Risk Management Strategies in the Handling of Natural Disaster Claims: A Phenomenological Study of Loss Adjuster Companies in Indonesia - Arief Prasojo Singgih (Jurnal Multidisiplin Indonesia, 2026)
Indonesia is highly vulnerable to natural disasters due to its location on active tectonic plates and within the Pacific Ring of Fire, exposing the country to earthquakes, tsunamis, floods, and landslides. The increasing frequency and severity of these events have placed significant pressure on the insurance sector, with surges in disaster claims impacting solvency and financial stability. This study aims to analyze adaptive risk management strategies employed by loss adjuster companies in handling natural disaster claims. Using a qualitative phenomenological approach with Interpretative Phenomenological Analysis (IPA), data were collected from 20 experienced loss adjusters through semi-structured interviews, supplemented by company documents, SOPs, and regulatory reports. Analysis revealed five emergent themes: multi-source risk identification, interpretative risk assessment, proximate cause determination, adaptive risk mitigation, and tacit knowledge-based decision making. These themes highlight that effective disaster claim management relies not only on formal procedures and technical evidence but also on professional experience, intuition, and continuous learning. The study concludes with a conceptual model of adaptive risk management, demonstrating that integrating evidence-based investigation, field experience, and tacit knowledge enhances decision quality, accountability, and organizational resilience. The findings provide theoretical insights and practical guidance for loss adjuster companies and regulatory bodies to strengthen disaster claim handling and risk management frameworks.